Education and Training in Making Herbal Soap Products in Puasana Village, South Konawe Regency - Lolok, Nikeherpianti; Fitriah, Wa Ode Ida; Saranani, Selpirahmawati; Dewi, Citra; Ridwan, Bai Athur (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
The community service program was carried out to provide education and training in making herbal soap products in Puasana Village, North Moramo District, South Konawe Regency. The Community Service activities aimed to provide knowledge for the community and skill processing by utilizing local natural ingredients to maintain health. The method used in carrying out this community service program is providing counselling regarding the properties of local medicinal plants as well as providing training in making herbal soap products from sago flour. This community service was accomplished by educating the target audience through presentations and providing training on how to make soap by demonstrating directly how to make soap from local, natural ingredients and how to package and label it. Instant herbal soap was formulated with base soap, sago flour, and oleum rosae fragrance (rose oil). Specific targets to be achieved are skill processing local natural ingredients into traditional cosmetic preparations as well as motivating the public to always maintain a healthy body. The implementation of education through counselling and making herbal soap as one of the community service programs carried out in Puasana Village has been carried out well and received good and inspiring responses. Counseling on the use of medicinal plants to be used as ingredients for making soap as well as the training provided hopefully will provide sustainable benefits to the Puasana Village community to increase their knowledge and skills in the use of nutritious plants.